Les cartes-marc de la història de Valter e Griselda de Bernat Metge i les del Griseldis de Petrarca. - ARTIGAS, MIQUEL MARCO (Scripta, 2013)
In 1388, Bernat Metge translated into Catalan a Latin text in which Petrarch had moved back story Decameron of Boccaccio, History of Walter and Griselda. The poet from Arezzo entitled his work De insigni obedientia et fide uxoria. Wrapping his version of the history, Petrarch sends both letters to his friend and author of the story. In these letters he exhibited mainly the reasons that led him to translate the text and makes some considerations about the behaviour of Griselda. Bernat Metge wraps also its translation with two letters and dedicated them to lady Elizabeth of Guimerà. This work aims to bring to the reader, first, a study of the enormous diffusion that this story had in the history of literature, and especially highlights the role played by translation of Petrarch in the disclosure of the history of Griselda. Secondly, it discusses the dating of the text considering various studies by critics especially during the last century. Also pay attention to the possible reasons that led to omit Metge authorship of the story that translates well even knew that the author was Boccaccio. And at the end of the work, we present a study about concepts such as Petrarch and Bernat Metge include on their letters, noting the similarities and differences found in both epistles. Taken into account, especially in this chapter, the previous contributions by critics in the course of this century, mainly, bringing strength and positioning clearly thought so as Petrarch as Metge regarding the interpretation of the attitude of the virtuous Griselda.